Emergence of a Promiscuous Peroxidase Under Non‐Equilibrium Conditions. Issue 2 (2nd December 2021) - Pal, Sumit; Reja, Antara; Bal, Subhajit; Tikader, Baishakhi; Das, Dibyendu
Abstract: Herein, we report the substrate induced generation of a transient catalytic microenvironment from a single amino acid functionalized fatty acid in presence of a cofactor hemin. The catalytic state accessed under non‐equilibrium conditions showed acceleration of peroxidase activity resulting in degradation of the substrate and subsequently led to disassembly. Equilibrated systems could not access the three‐dimensional microphases and showed substantially lower catalytic activity. Further, the assembled state showed latent catalytic function (promiscuity) to hydrolyze a precursor to yield the same substrate. Consequently, the assembly demonstrated protometabolism by exploiting the peroxidase‐hydrolase cascade to augment the lifetime and the mechanical properties of the catalytic state. Abstract : Substrate‐induced generation of a transient catalytic microphase was shown in presence of a single amino acid functionalized fatty acid and a cofactor hemin. The transient state exhibited acceleration of catalytic potential resulting in degradation of the substrate. Furthermore, latent catalytic function was displayed to hydrolyze a precursor to yield the same substrate suggesting promiscuous activity.